TERPENUHIKAH UNSUR PIDANA PENGUASAAN TANAH YANG SAMA-SAMA BELUM MEMILIKI SERTIFIKAT TANDA BUKTI HAK - Edwin Yuliska (Ensiklopedia Social Review, 2020)
Law in Indonesia adheres to the Continental European legal system which is divided into two groups, namely the field of public law and the field of private law. Public law is a law that has a scope of legal subject to dispute with legal objects, namely state administration law, state administrative law, and criminal law. While private law is a field of law that has the scope of affairs of legal subjects that conflict with other legal subjects. But sometimes law enforcement often fails to understand these two legal systems, which cannot distinguish between criminal and civil ones, thus confusing civil cases that are made criminal cases and criminal cases used as civil cases for various reasons.